EKSISTENSI PERKUMPULAN TRIDHARMA KEBAYORAN, JAKARTA SELATAN DALAM MEMPERTAHANKAN AGAMA BUDAYA LELUHUR ETNIS TIONGHOA - Widianto, Bimo Rafi (Studi Budaya Nusantara, 2022)
The purpose of this study was to determine the existence of the Tridharma Kebayoran Lama association in South Jakarta in defending the religion and culture of the Chinese ethnic ancestor. The method used is descriptive qualitative by using the collection of library sources that are loaded through google scholar in the form of journalsand books as well as the official website of the Tridarma.or.id association whose sources can be accounted for. The result of this research is that tridharma is a teaching that combines the three teachings of Confucianism, Taoism and Buddhism which was pioneered by Lin Chao En during the Ming dynasty (1368-1644). The three teachings were brought by the Chinese ethnicity when trading in Indonesia. In its development, the Tridharma association developed in 1920 in Jakarta which was pioneered by Kwee Tek Hoay who had aspirations to protect Chinese religion and culture from the onslaught of western missionaryism. This association still exists until now, it is engaged not only in the field of religion but also in the social field.